-5x=3y

The slope-intercept form is y=mx+b, where m is the slope and b is the y-intercept.

y=mx+b

Rewrite the equation as 3y=-5x.

3y=-5x

Divide each term by 3 and simplify.

Divide each term in 3y=-5x by 3.

3y3=-5×3

Cancel the common factor of 3.

Cancel the common factor.

3y3=-5×3

Divide y by 1.

y=-5×3

y=-5×3

Move the negative in front of the fraction.

y=-5×3

y=-5×3

Rewrite in slope-intercept form.

y=-53x

y=-53x

Using the slope-intercept form, the y-intercept is 0.

b=0

Find the Y-Intercept -5x=3y